2018
DOI: 10.1016/j.ejps.2018.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Topical treatment with a transient receptor potential ankyrin 1 (TRPA1) antagonist reduced nociception and inflammation in a thermal lesion model in rats

Abstract: Thermal injury promotes tissue inflammation and pain, which is difficult to control. Different peripheral mechanisms seem to be involved in burn pain, such as free radical-induced damage, but further study is still needed to understand how oxidant substances induced nociceptor sensitization. The transient receptor potential ankyrin 1 (TRPA1) is an ion channel activated by oxidants substances, and it could be sensitized after tissue inflammation. This study evaluated the TRPA1 involvement in nociception and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 105 publications
(165 reference statements)
0
10
0
1
Order By: Relevance
“…Topical administration may help overcome such prob lems. Indeed, a topical HC030031 gel (0.05%) reversed mechanical and cold allodynia in mice after ultraviolet B induced burn injury 90 . This implies a therapeutic value for TRPA1 antagonist creams for patients with sunburn pain or thermal injury.…”
Section: Familial Episodic Pain Syndromementioning
confidence: 97%
“…Topical administration may help overcome such prob lems. Indeed, a topical HC030031 gel (0.05%) reversed mechanical and cold allodynia in mice after ultraviolet B induced burn injury 90 . This implies a therapeutic value for TRPA1 antagonist creams for patients with sunburn pain or thermal injury.…”
Section: Familial Episodic Pain Syndromementioning
confidence: 97%
“…TRPA1 ablation results in reduced inflammation and fibrosis/scarring in the corneal stroma during wound healing (626). At the level of the skin, it was recently shown that HC-030031 has antinociceptive and anti-inflammatory effects after thermal injury (183,287). (457,735,736,823,849), where it is involved in the spontaneous peptide hormone exocytosis (800) and its ablation decreases mature oligodendrocyte apoptosis and thereby demyelination and behavioral alterations and morphological changes induced by cuprizone (115,700).…”
Section: Trpa1 and Inflammationmentioning
confidence: 99%
“…TRPM8 expression may directly influence the thermal pain threshold given that TRPM8 blocker reduced TRPM8 expression in CCI rats (Figure 2). There may be correlations between TRPM8 and other thermo-sensitive receptors, such as Nav1.7,33 TRPA134 and TRPV1,35 which need further research to detect the expression of these receptors when TRPM8 was blocked.…”
Section: Discussionmentioning
confidence: 99%